Dynamic response and microstructure evolution of the finite steel target subjected to high velocity impact by copper explosively formed projectile. Issue 12 (21st June 2017) - Liu, J.F.; Long, Y.; Ji, C.; Zhong, M.S.
Abstract: The dynamic deformation of the finite steel target subjected to high velocity impact of copper explosively formed projectile is investigated by optical, scanning, and transmission electron microscopy. Morphology analysis of fracture surfaces indicates that the copper remainder plated to the crater wall shows extremely plastic deformation, which consists of elongated parabolic dimples, and the mild carbon steel target exhibits excellent brittle features that material fails mainly along the cleavage facets on the rear surface of target under strong impact of explosively formed projectile. In the surface of crater, the whole part of copper remainder and partial material of steel target undergoes completely dynamic recrystallization. The layer thickness of dynamic recrystallization zone, which displays an extreme plastic flow in solid state, is about 21.3 μm in steel target, and the average size of the refined grains significantly decreases to approximately 200 nm. Theoretically calculated results indicate that the temperature increase is associated with shock wave and plastic deformation of steel target and can reach 1352 K, which is 0.75 T m (where T m is the melting temperature of steel target). The change in microhardness from the crater wall to the matrix of target is consistent with micro‐deformation of grains, and maximum microhardness is observed on the interface between dynamic recrystallization and severe plastic deformation zones of steel target.